اسلامی عدالت اور مجرمانہ قانون: قصاص، دیت اور تعزیرات کے نفاذ کا تجزیاتی مطالعہ: ISLAMIC COURTS AND CRIMINAL LAW: AN ANALYTICAL STUDY ON THE IMPLEMENTATION OF QISAS, DIYAT, AND TA’ZIR (Al-Aasar, 2026)
This study presents a detailed analytical examination of the practical and jurisprudential aspects of the implementation of Islamic courts and criminal law, with a particular focus on the systems of Qisas (retribution), Diyat (blood money), and Ta’zir (discretionary punishments). The paper primarily relies on Islamic jurisprudence (Fiqh), the Qur’an, Sunnah, consensus (Ijma’), and authentic classical texts to provide a scholarly assessment of the legal and theoretical framework of Islamic courts, judicial powers, and the role of the state.The research begins with an exploration of the concept of Islamic courts, their historical evolution, and judicial system, including a detailed analysis of the qualifications of judges (Qadis), criteria for appointment, jurisdiction, judicial autonomy, and accountability mechanisms. Subsequently, the theoretical framework of Islamic criminal law is elaborated, addressing the definition of crime in Sharia, principles of legal responsibility, and the hierarchical categorization of Hudud (fixed punishments), Qisas, Diyat, and Ta’zir.The study examines the implementation of Qisas, its conditions, impediments, and the role of the victim’s guardian (Wali-dam) or the state. The analysis demonstrates that Qisas is not merely punitive but also serves to establish justice, deter crime, and protect human life. The study further explores the system of Diyat, analyzing its amount, types, payment mechanisms, the role of ‘Aqilah (relatives of the victim), and its application in contemporary legal frameworks. The discussion of Ta’zir addresses judicial discretion, the scope of discretionary punishments, types of penalties, and their reformative objectives.The paper also emphasizes evidence and the law of testimony, discussing confession, witness testimony, circumstantial evidence, oath-taking (Qasamah), and modern forensic evidence, highlighting their jurisprudential validity and judicial applicability. It demonstrates that the Islamic judicial system is founded on justice, transparency, and the accurate identification of crimes, while modern technological and forensic tools can be integrated in accordance with Sharia principles.The study also examines the role of the state in enforcing criminal law, including the interaction between the judiciary and administrative authorities, practical challenges, and obstacles, along with recommendations for reform and efficiency within contemporary social and legal contexts. A comparative analysis with modern legal systems is provided, considering Islamic and Western criminal law, human rights, and international legal standards, highlighting the utility and purposive nature of Islamic punishments.The findings indicate that the Islamic criminal law system, through Qisas, Diyat, and Ta’zir, upholds the principles of justice, reform, social protection, and human rights. The objective of punishment is not merely retribution but also aims to maintain social order, provide moral education, reform the offender, and ensure the establishment of justice. Through scholarly references, jurisprudential reasoning, and practical applicability, this study elucidates the comprehensive and purposive nature of the Islamic judicial system and its compatibility with modern legal, social, and international frameworks.